1981
DOI: 10.1038/icb.1981.56
|View full text |Cite
|
Sign up to set email alerts
|

CHANGES IN SOMATOMEDIN‐LIKE ACTIVITY AND GROWTH HORMONE CONCENTRATIONS IN THE PLASMA OF THE DOMESTIC FOWL (GALLUS DOMESTICUS)

Abstract: Summary. Variations to immunoreactive growth hormone (GH) and bioassayable somatomedin-like activity (SLA) were determined in the plasma of the domestic fowl. The plasma concentralions of SLA (potency relative to a pooled serum standard) and GH were both inversely age-related in growing cockerels (Thornber 909) between 3 and 20 weeks of age (SLA, r = 0 454; P<0 01. GH. r = 0 548; P<0 01) and directly related to each other (r -0 54, P<0 01). In immature birds maintained on a photoperiod of 16 h light, 8 h darkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
3

Year Published

1984
1984
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
4
3
Order By: Relevance
“…However it is arguable whether a real discrepancy exists between the data obtained by bioassay and by radioimmunoassay. Falconer et al (1981) reported a significant 29% decrease in bioassayable somatomedin activity after a 24-h fast while, in the present study, starvation for 12-48 h was accompanied by a non-significant 20% decline in plasma IR-somatomedin-C concentrations. In rats, plasma concentrations of IR-somatomedin-C are found to be decreased by starvation for 24 h (Maes et al 1983).…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…However it is arguable whether a real discrepancy exists between the data obtained by bioassay and by radioimmunoassay. Falconer et al (1981) reported a significant 29% decrease in bioassayable somatomedin activity after a 24-h fast while, in the present study, starvation for 12-48 h was accompanied by a non-significant 20% decline in plasma IR-somatomedin-C concentrations. In rats, plasma concentrations of IR-somatomedin-C are found to be decreased by starvation for 24 h (Maes et al 1983).…”
Section: Discussioncontrasting
confidence: 60%
“…This contrasts with the observed effect of starvation on plasma somatomedin bioactivity of young chicks (Falconer et al 1981). However it is arguable whether a real discrepancy exists between the data obtained by bioassay and by radioimmunoassay.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations